Bem-te-vejo: Connecting people and mental health professionals to promote care in the face of depression signs - Aguiar, Yago; Morais, Samuel de; Medeiros, Maria; Andrade, Lucas; Pereira, Jessye Kessia de Carvalho; Souza, Damires Yluska; Rêgo, Alex Sandro da Cunha; Mendes, Roberto (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas_estendido.2026.26522, 2026)
Mental health is a global challenge. In Brazil, depressive disorders have a high incidence, often undiagnosed and with limited treatment, especially in vulnerable areas. Digital technologies offer means for transforming healthcare models through telehealth, reducing geographical and socioeconomic barriers. This work presents the “Bem-te-vejo” platform, a conversational agent designed to promote connection between individuals and mental health professionals in the face of depression signs. The solution proposes continuous care, supporting people and mental health policies. An evaluation based on the Technology Acceptance Model has been conducted with mental health professionals and potential users, who indicated good acceptance and intention to use.